Embedded Systems Design for High-Performance Medical Applications - Venudhar Rao Hajari; Abhip Dilip Chawda; Prof.(Dr.) Punit Goel; A Renuka; Lagan Goel (Innovative Research Thoughts, 2024)
Advancements in patient care and diagnostic accuracy have been driven by the emergence of embedded systems, which has had a dramatic influence on the design and implementation of high-performance medical applications. This abstract explores the fundamental features of embedded system design that are specifically designed for medical applications. Particular attention is paid to the optimization of performance, the dependability of the system, and its integration within demanding healthcare contexts. When it comes to real-time processing, precision, and safety, embedded systems in medical devices are required to fulfill several severe standards. For the purpose of improving the performance of embedded systems that are used in high-performance medical applications, this article provides an overview of the important design considerations and tactics that are involved. Embedded systems are specialized computer systems that are situated inside a larger device and are responsible for performing certain duties. When it comes to the realm of medicine, these systems are an essential component of many technologies, including imaging machines, patient monitoring systems, and diagnostic instruments. The necessity for high dependability and real-time processing poses a unique set of issues when it comes to the design of embedded systems for use in medical applications. To guarantee the operation of the system, it is necessary to address concerns such as the amount of power used, the integrity of the data, and the capability to function in a variety of environments.